Nutrient uptake, osmolytes and antioxidant potential of different citrus rootstocks subjected to acidic soils - DEVACHANDRA, NONGTHOMBAM; AWASTHI, O P; SHARMA, V K; PANDEY, RAKESH; PRAKASH, JAI; SHANKAR, KRIPA (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during 2021–23 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the response of five citrus rootstocks, viz. Rangpur lime (RL); Troyer citrange (TC); Cleopatra mandarin (CM); X-639 and Jatti khatti (JK) for leaf and root nutrient content including osmolytes and antioxidant potential in a soil pH range of 3.8–7.5. The experiment was initiated after the final establishment of plants in the pots in a factorial completely randomized block design (Factorial-CRBD) with four levels of soil pH and five different citrus rootstocks. Result indicated that RL recorded highest phosphorous content in leaf (0.43%) and root (0.36%) as well as total soluble sugars content (9.34 mg/g) in leaf. TC registered highest content of nitrogen (1.83%) and phosphorous (0.35%) in root; potassium (1.83 and 1.89%) and calcium (1.10 and 0.94%) in leaf and root, respectively, while significantly higher magnesium content (0.77%) and soluble protein (5.67 mg/g) were documented in the leaf as compared to other rootstocks. Maximum nitrogen content (3.10%), total phenols (6.76 GAE mg/g) and proline (40.27 μmol/g) were registered in leaves of CM whereas magnesium content in root (1.05%). The nitrogen content in leaves and roots of all the rootstocks as well as total soluble sugar tended to increase with decreasing levels of soil pH. Principal component analysis identified a distinct cluster of rootstocks comprising TC, X-639 and JK grouped together with notably high phenolic levels, while RL formed a separate cluster characterized by higher concentrations of total soluble sugar, proline and phosphorus. Thus, the present study demonstrated that citrus rootstocks prefer relatively lower soil pH for optimal growth. Among the investigated rootstocks, RL has demonstrated the ability to tolerate higher acidic soil conditions.